Abertura financeira e a incidência e recuperação da crise financeira global de 2008-2009 - Oliveira Júnior, Marcos Santos de (2019)
The main goal of this work is to analyze the role of financial openness in the incidence and recovery of the global financial crisis in the period 2008-2009. Chapter 1 reviews the theoretical literature on the possible effects of financial openness. The potential risks of financial openness are increased macroeconomic instability and financial crises, the possible benefits are consumption smoothing and economic growth. Chapter 2 presents the global financial crisis, origin, spread and the main channels of transmission. In addition, the chapter analyzes, through descriptive statistics, some of the stylized facts associated with the crisis and the behavior of financial openness. The results suggest that: i) the crisis severity was greater for the advanced economies than for developing economies; ii) the advanced economies presented higher financial openness than developing economies; ii) advanced economies showed better post-crisis recovery than developing economies. Chapter 3 conducts an econometric investigation about the effects of financial openness on incidence and recovery of the global financial crisis for a dataset of up to 148 economies, 34 advanced and 114 developing in the period 1990-2010, to measure the incidence and recovery of the financial crisis this work uses linear regression models OLS for cross-section data and to test the joint significance of the variables, the Bayesian Model Averaging (BMA) model with MCMC algorithm, Monte Carlo via Markov Chains (MC3) is used. The results show the following pattern: i) There is systematic statistical evidence for the facto index LMF, that the crisis was less severe in countries with greater financial openness; ii) There is systematic statistical evidence for Schindler Fernandez's de jure openness index, that the crisis was less severe in countries with greater financial openness. The results for crisis recovery suggest: i) there is significant statistical evidence for the LMF index of financial openness that the recovery was slower in countries with greater financial openness; ii) there is no statistically significant relationship between de jure openness indices and the recovery of the financial crisis. The paper contributes to the literature in three dimensions: i) a systematic study of the effect of financial openness on the incidence and recovery of the global financial crisis; ii) a wide range of financial, de jure and de facto open indexes are used, including the index with the new methodology adopted by the IMF; iii) Bayesian Model Averaging is used to test the joint significance of a broad and diverse set of explanatory variables.